Research involving anxiety in non-human primates has potential implications for the assessment and treatment of anxiety in autism spectrum disorder: A translational literature review. (3rd May 2016) - Gonzales, Heather K.; O'Reilly, Mark; Lang, Russell; Sigafoos, Jeff; Lancioni, Giulio; Kajian, Mandana; Kuhn, Michelle; Longino, Deanna; Rojeski, Laura; Watkins, Laci
Abstract: Objective : The purpose of this translational review (i.e. moving from basic primate research toward possible human applications) was to summarize non-human primate literature on anxiety to inform the development of future assessments of anxiety in non-verbal individuals with autism spectrum disorder (ASD). Methods : Systematic searches of databases identified 67 studies that met inclusion criteria. Each study was analysed and summarised in terms of (a) strategies used to evoke anxiety, (b) non-verbal behavioural indicators of anxiety and (c) physiological indicators of anxiety. Results : Eighteen strategies were used to evoke anxiety, 48 non-verbal behavioural indicators and 17 physiological indicators of anxiety were measured. Conclusions : A number of the strategies used with non-human primates, if modified carefully, could be considered in the ongoing effort to study anxiety in individuals with ASD. Potential applications to the assessment of anxiety in humans with ASD are discussed.